(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
The present article introduces a very synthetical insight into Portugal’s healthcare situation and its position with regards to countries that have a similar degree of development. It describes the enduring inequities and in particular the fact that health-related costs have a significant importance with regards to the GDP and the fact that such costs are disproportionate to their amplitude and quality.The article also specifies the process of healthcare delivery and the crucial role played by the doctor and the drugs. Following a brief depiction of the pharmaceutical industry, we analyze the relation between pharmaceutical marketing and the doctor as prescriber.Two aspects are highlighted in the analysis: the importance of information in the medical prescription and the profound asymmetry between information conveyed by the pharmaceutical industry and independent information. This asymmetry throws into relief the relation between the intensity of the prescription of a given brand and the intensity of the information that the pharmaceutical industry sends out to the prescriber. In addition, the article analyses the means used by the industry to promote its products and their significance in the companies’ spending structures; it also points out inappropriate practices and measures that strive to limit its negative effects.